PENGARUH OBAT KUMUR TERHADAP KONDISI MUKOSITIS PASIEN KANKER RONGGA MULUT YANG MENERIMA KEMOTERAPI DAN RADIOTERAPI - fika faradillah drakel; riani setiadhi (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2022)
Introduction: Oral cancer, also known as mouth cancer, is a malignancy that develops in any part of the oral cavity. Oral cancer can occur on the lips, tongue, gums, cheek, and mucosa of the palate. Oral cancer therapy includes chemotherapy and radiotherapy which can cause side effects, one of them is oral mucositis. Oral mucositis is one of the most common complications of cancer therapy. The main complaint of patients with mucositis is pain which is characterized by clinical features in the form of an erythema, bleeding, and ulceration. Mouthwash has been widely used as an antimicrobial compound and topical prophylactic agent against oral mucositis. The purpose of this literature is to explain the differences between mouthwashes used and the one that produce a better therapeutic effect. Review: Mouthwash used to treat mucositis in several studies in the literature is saline, 0.12% chlorhexidine and 5% bicarbonate, and propolis. The results showed that the use of saline only provided moisture to the ulcerative area but did not suppress any pain. While the combination of 0.12% chlorhexidine and 5% bicarbonate has a healing effect for five to seven days. The propolis mouthwash has a healing effect for 14 days but only for adult patients. Conclusion: The study of mouthwash had many advantages and disadvantages against oral mucositis, but the mouthwash with a combination of 0.12% chlorhexidine and 5% bicarbonate had a good analgesic effect for patient with oral cancer.